Decompositions of 3-uniform hypergraph K v (3) into hypergraph K 4 (3) + e - Feng, Tao; Chang, Yanxun (Utilitas Mathematica, 2012)
In this paper it is established that a decomposition of a 3-uniform hypergraph K v (3) into a special kind of hypergraph K 4 (3) + e exists if and only if v = 0,1,2 (mod 5) and v ≥ 7.